Tailoring the molecular structure of crosslinked polymers for pervaporation desalination - Xue, Yun Long; Huang, Jin; Lau, Cher Hon; Cao, Bing; Li, Pei (Nature communications, 2020)
Polymer crosslinking imbues chemical stability to thin films at the expense of lower molecular transportation rates. Here in this work we deployed molecular dynamics simulations to optimise the selection of crosslinking compounds that overcome this trade-off relationship. We validated these simulations using a series of experiments and exploited this finding to underpin the development of a pervaporation (PV) desalination thin-film composite membrane with water fluxes reaching 234.9 ± 8.1 kg m −2 h −1 and salt rejection of 99.7 ± 0.2 %, outperforming existing membranes for pervaporation and membrane distillation. Key to achieving this state-of-the-art desalination performance is the spray coating of 0.73 μm thick crosslinked dense, hydrophilic polymers on to electrospun nanofiber mats. The desalination performances of our polymer nanocomposites are harnessed here in this work to produce freshwater from brackish water, seawater and brine solutions, addressing the key environmental issue of freshwater scarcity. Polymer crosslinking in desalination membranes adds stability on the cost of molecular transportation rates through the membrane. Here the authors tailor crosslinking of desalination membranes to overcome the stability and transport trade-off, and demonstrate a pervaporation desalination thin-film composite membrane with high water flux.